DIMENSIONS OF THE SCIENCE LITERACY LEARNING ENVIRONMENT: SYSTEMATIC LITERATURE REVIEW USING THE PRISMA METHOD - Siska Merrydian; Wardani Rahayu; Yuli Rahmawati (Adisam Publisher, 2025)
This systematic literature review attempts to analyze various dimensions related to measuring the scientific literacy learning environment. Scientific literacy skills for students are very important in preparing to face the challenges of the modern world. Learning environments that support scientific literacy enable students to develop a holistic understanding of science and technology, including how science can be used to protect the environment and confront global threats. One approach to literature study is Systematic Literature Review (SLR). This research uses a Systematic Literature Review using the Prisma Method with the help of a VOS viewer. This research was limited by only searching for Scopus journal articles published in 2019-2024. Based on one hundred and nineteen (119) articles reviewed, through a systematic literature review process, with an article publication period between 2019 and 2024, the results were that only twenty (20) articles met the criteria and were used as references in this research. Based on the results of the systematic literature review analysis, it was concluded that the dimensions of the scientific literacy learning environment consisted of: science phenomena, science investigations, interest in science in free time, enjoyment of science, teacher support, student cooperation/cohesion, and the social implications of science.